THE MILITARY AS A CONTRIBUTOR TO NATIONAL DEVELOPMENT - A.D. Shaw (Scientia Militaria, 2012)
In the last two decades there has been a marked increase in the involvement of military forces in development activities that have traditionally been outside the military sphere. This trend has been particularly evident in Third World countries, where the need for social development is most pressing.